(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of the study is to determine the place of the literary environment, to study the creative laboratory and evaluate the attitude to the problem of personality in the formation of the artistic thinking of the author of the divan, the bilingual poetess Mohlaroyim-Nadira in the context of the era. The issue of the role of the literary environment of Kokand in the formation of the artistic thinking of the poetess was comprehensively analyzed on the basis of a separate historical-comparative method, and using the hermeneutical method, it was included in a special framework of the study. As a result of the study, the following factors can be noted that formed the artistic worldview of Nadira: a) the efforts and teaching of her husband Umarkhan; b) instruction by Jahan Atin Uvaisi; c) the literary connection of the poets who worked under the direction of Nadira. The following conclusions were made: Firstly, the literary environment of Kokand, which was formed in the first half of the 18th century under the rule of the Kokand Khanate, reached its peak during the reign of Amir Umarkhan. The literary environment played an important role in the formation of Nadira as a poetess of the era. In particular, the artistic thinking of Nadira was improved under the influence of the efforts of her husband Umarkhan and the instruction of Jahan Atin Uvaisi, while the literary connection of the poets who worked under the guidance of the poetess Nadira played an important role. Secondly, after her fiance’s, Umarkhan’s death, Nadira played great role in developments in Fergana. Contributing to the development of the literary environment, she left her mark as a major figure in the Uzbek literature of the first half of the 19th century, who managed to rise to the level of mentor and patronage. Thirdly, Nadira’s lyrics were able to embody in their essence the ideas of love, fidelity, humanity, justice and faith. The lyrics of the poetess are important because in her lyrical works she sang the ideas of goodness, a good name and a good deed in life. Her lyrics evoke a sense of enthusiasm in people’s hearts. This situation proves that the poetess is a worthy heir to the literary environment of Kokand.